Influenza antivirals currently in late‐phase clinical trial. Issue 3 (28th February 2017) - Koszalka, Paulina; Tilmanis, Danielle; Hurt, Aeron C.
Abstract : Influenza antiviral drugs are important for the control of influenza, most specifically for the treatment of influenza patients with severe disease following infection with a seasonal influenza virus, a newly emerging influenza strain, or in the event of a pandemic. Many influenza antivirals that are currently under investigation in late‐stage clinical trials differ in their mechanism of action compared to drugs currently licensed for the treatment of influenza. Nitazoxanide and DAS181 target components of the host cell and alter the ability of the virus to replicate efficiently, while small molecule drugs such as T705, JNJ63623872 and S‐033188 bind to the viral polymerase complex and restrict viral replication. Monoclonal antibodies that are currently in clinical trial for the treatment of influenza most commonly are targeted to the stem region of the haemagglutinin molecule. Early findings from animal models and in vitro studies suggest that many of the new antiviral drugs when tested in combination with oseltamivir have improved effectiveness over monotherapy. Clinical trials assessing both monotherapy and combination therapy are currently under investigation. It is hoped that as new antivirals are licensed, they will improve the standard of care and outcomes for influenza patients with severe disease.